Assessing version control system skill gaps in undergraduate IT education: A needs assessment of academic and industry stakeholder perspective - Kulchan, Supeeti; Pimdee, Paitoon; Sukkamart, Aukkapong (Edelweiss Applied Science and Technology, 2025)
This study presents a needs assessment evaluating undergraduate Information Technology (IT) students' Version Control System (VCS) competencies based on perspectives from IT instructors and IT entrepreneurs in Thailand. Using a structured questionnaire, data were collected from 49 stakeholders assessing both actual and desired skill levels across seven core VCS competencies. Paired-sample t-tests revealed statistically significant differences between actual and desired competencies for all skill factors (p < .01), underscoring considerable gaps. The highest Priority Needs Index (PNImodified) values were observed in writing effective commit messages, detecting and resolving errors, and tracking change history. Notably, instructors perceived more significant skill gaps than entrepreneurs, highlighting a need for improved curriculum alignment. The findings emphasize the urgency of enhancing higher-order VCS skills critical for agile and DevOps workflows. This study lays the groundwork for developing a new training curriculum integrating blended learning, problem-based learning (PBL), and generative AI tools to address these gaps and better prepare students for professional software development environments.